2017
DOI: 10.29309/tpmj/2017.24.01.484
|View full text |Cite
|
Sign up to set email alerts
|

Breast Abscess;

Abstract: Objectives: To compare the recurrence rate between incision drainage andmultiple needle aspiration for breast abscess treatment. Study Design: Randomized ControlledTrial. Setting: Department of General Surgery, Bahawal Victoria Hospital, Bahawalpur. StudyDuration: 29th September 2015 to 29th June 2016. Materials & Methods: A total of 60 femalepatients with breast abscess of <2 cm in size and of duration <2 weeks between 20 to 40 yearsof age were included. Patients with multiple breast abscesses, recu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Several studies have reported shorter resolution time with needle aspiration compared with I&D and less scar formation, though there was a higher failure rate in the aspiration group compared to open drainage [7,[14][15][16]. Despite the potential need for repeat intervention, patients may prefer minimally invasive percutaneous aspirations due to early resumption of breastfeeding, improved cosmesis, less pain, and no hospitalization [11,[15][16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have reported shorter resolution time with needle aspiration compared with I&D and less scar formation, though there was a higher failure rate in the aspiration group compared to open drainage [7,[14][15][16]. Despite the potential need for repeat intervention, patients may prefer minimally invasive percutaneous aspirations due to early resumption of breastfeeding, improved cosmesis, less pain, and no hospitalization [11,[15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Breast abscesses are a common finding in puerperal women [ 6 ]. This may be due to predisposing factors such as mastitis and the proliferation of glandular tissue in the breast which commonly occurs during lactation [ 7 - 9 ]. A majority of patients in our study had lactation-associated breast abscesses which are consistent with previous reports [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast abscess is thought to occur in 0.4% to 3% of mastitis patients in women 6 . The likelihood of developing a lactational breast abscess increases with maternal age at birth, gestational age >41 weeks, mastitis, primiparity, difficulty breastfeeding in the hospital and cracked nipples 7,8 . An ultrasound scan is used to confirm a clinical diagnosis of lactation breast abscess 9,10 .…”
Section: Introductionmentioning
confidence: 99%